MANAJEMEN PRODUKSI SANGGAR TARI DAN MUSIK BOUGENVILLE DI KOTA PONTIANAK - Wildan Aprian Pratama; Nurmila Sari Djau; Yudhistira Oscar Olendo (Universitas Tanjungpura, 2021)
ABSTRACTThis research aims to describe the management of Bougenville Dance and Music Galerry in Pontianak City. Bougenville Dance and Music Center is an art center that still exists in Pontianak City. This research is qualitative descriptive research. The subject of this study was Bougenville Dance and Music Center in Pontianak City. The research focused on the study of the exposure of the production management of the galerry. The data was obtained with hands-on observation techniques, in-depth interviews, and documentation studies. The data is analyzed with qualitative descriptive analysis techniques. The validity of data obtained through triangulation through the source stage, namely checking data from various sources. The source is the result of observations, interviews, and documentation about bougenville Dance and Music Art Center in Pontianak City. This study obtained the following results; (1) Bougenville Dance and Music Arts Center uses a form of family organization and openness, (2) management applied in the galerry using traditional management, (3)The management function at Bougenville Dance and Music Arts Center is on planning, organizing, implementing, and supervising. .Keywords: Management, Art Production, Bougenville Dance and Music Gallery